Molecular Characteristics of ST1193 Clone among Phylogenetic Group B2 Non-ST131 Fluoroquinolone-Resistant Escherichia coli - Wu, Jing; Lan, Fangjun; Lu, Yanfang; He, Qingwen; Li, Bin (Frontiers in Microbiology, 2017)
Objectives Sequence type (ST) 1193 is emerging as a new, virulent and resistant lineage among fluoroquinolone resistant Escherichia coli (FQr E. coli). In this study, we investigated the prevalence and molecular characteristics of this clone isolated from a Chinese university hospital. Methods 73 phylogenetic group B2-FQr-non-ST131 isolates were collected from August 2014 and August 2015 at a Chinese university hospital. Isolates were screened for ST1193 by Multilocus sequence typing (MLST). E. coli ST1193 then underwent lactose fermentation determination, susceptibility testing, virulence genotyping, PCR-based O typing, pulsed-field gel electrophoresis (PFGE) and FQr mechanism analysis. Results Of 73 B2-FQr-non ST131 E. coli isolates, 69.9% (n=51) were ST1193. 90.2% (46/51) of ST1193 isolates were O75 serotype and 96.1% (49/51) of the ST1193 isolates were lactose non-fermenters. 35 clusters were identified by PFGE. ST1193 isolates exhibited a set of 3 conserved mutations defining quinolone-resistance determining region (QRDR) substitutions (gyrA S83L, D87N, and parC S80I). The most frequent VF genes detected in these E. coli ST1193 isolates were fyuA (yersiniabactin, 96.1%), fimH (type 1 fimbriae, 94.1%), iutA (iron uptake gene, 90.2%), kpsMT II (group II capsule, 90.2%), kpsK1 (K1 capsule, 86.3%) and PAI. Conclusion ST1193 lineage accounts for the majority of group B2-FQr-non-ST131 E.coli clinical isolates. Most of the ST1193 are serotype O75 and lactose non-fermenting. Strategic surveillance and control schemes are needed in the future for this newly emerging clone of E. coli: B2-FQr-ST1193.